The Spread of Sufism and Its Supporting Factors in Europe - Nengsih, Afnida; Rinaldi , Rinaldi; Trisasmita, Rio (Universitas Cokroaminoto Yogyakarta, 2025)
Sufism has existed for a long time in the Western world, especially in Europe. However, it continues to develop amidst the rejection of Islam. It has become an alternative for European society as a solution to the moral and psychological crisis, according to the views of some people in Europe and the Western world. The article's writing was carried out using a literature study with a descriptive analysis approach assisted by inductive historical aspects, which produced a new perception of the development of Islamic Sufism in the West, especially in Europe. Western thought is based solely on materialism, which no longer considers religion, human relationships with God, and human relationships related to divine rules. People who participate in the teachings of Sufism want to find peace of mind away from the exploitation of fellow humans and the material world, which no longer humanizes humans. The phenomenon of Islamic Sufism being transmitted to Western countries and its embrace by many thinkers and intellectuals has produced new issues and problems that have proven the extent of the fertility of Islamic thought in general and the extent of the richness of Sufism in particular and its ability to break into the strongest material civilizations and brand them with its spiritual character. Likewise, the liberation of women in Western countries and their desire to show Leadership and excellence are found in Sufism.